WHO ARE AMERICANS? ANALYSIS OF OBAMA AND TRUMP’S POLITICAL SPEECHES ON IMMIGRATION - Tinshe, Sonia; Junaidi, Junaidi (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2019)
Immigration has been a crucial discussion in the American politics ever since the nation was still writing its constitution. Seeing how immigrants have shaped the American society, it is important to see how they are perceived, as minorities, by significant political figures, such as the president. The objective of this paper is to understand the ideology behind Obama and Trump’s political speeches about immigration, as well as its relevance to the political discourse and social context in America. Five political speeches from Obama (2009-2014), as well as two political speeches from Trump (2016-2017) are analyzed, as the primary data, using Critical Discourse Analysis, particularly Fairclough’s (1993) three-dimensional framework. The finding shows that Obama’s and Trump’s ideology on immigration is related with their idea of the immigrant’s identity in American society. It is shown through their word choice, such as pejorative adjective, and the theme related with the issue of immigration. Seen from the political discourse, the speeches are showing perceived superiority that the presidents have over immigrants. Moreover, from the social perspective, it dehumanizes and reduces the identity of immigrants.